INVESTIGATION OF LONG-WAVELENGTH INFRARED RADIATION DETECTION MECHANISMS IN A GAS-DISCHARGE SEMICONDUCTOR PHOTOGRAPHIC IONIZATION CAMERA - Utamuradova, Sh.B.; Xaydarov, B.Z. (Research Focus International Scientific Journal, 2026)
Physical processes in gas-discharge cells with semiconductor electrodes were investigated theoretically and experimentally. Plasma contacts were found to enhance the stability of gas-discharge luminescence. A semiconductor photographic ionization camera with an additional damping cascade enabled object detection in the infrared range of 0.38–11 μm and beyond. The experimental results were in good agreement with theoretical calculations.